Understanding hunter-wild pig (Sus scrofa) interactions in the United States: a mixed-methods research approach to inform invasive species management - McLean, Hailey E., author; Bright, Alan, advisor; Teel, Tara, committee member; Champ, Joseph, committee member; Shwiff, Stephanie, committee member (Colorado State University. Libraries, 2020)
To view the abstract, please see the full text of the document.